Metformin‐Associated Lactic Acidosis During Docetaxel Therapy for Castration‐Resistant Prostate Cancer: A Case Report - Y. Inoue; A. Niimi; T. Kudo; U. Yoshizaki; Y. Sato; H. Kume (IJU Case Reports)
ABSTRACT Introduction Docetaxel is a key treatment for castration‐resistant prostate cancer and is administered with prednisolone, which increases the risk of steroid‐induced diabetes. Its myelosuppressive effect also increases vulnerability to febrile neutropenia. Metformin is widely used for glycemic control; however, elderly cancer patients are particularly susceptible to metformin‐associated lactic acidosis, necessitating careful management of sick‐day and febrile neutropenia during chemotherapy. Case Presentation We report a 70‐year‐old male with castration‐resistant prostate cancer and diabetes mellitus who developed febrile neutropenia on Day 5 following docetaxel initiation. He progressed to shock with severe metabolic acidosis on Day 7 and died despite intensive care, including continuous renal replacement therapy. A retrospective review revealed continued metformin use despite prodromal fatigue and loss of appetite, likely due to impaired judgment. Conclusion This case may have involved septic shock, but metformin likely worsened the lactic acidosis. It highlights the need for sick‐day education and monitoring in elderly cancer patients.